The Role of Village Government in Managing Village Funds Based on the Regulation of the Minister of Home Affairs Number 20 of 2018 on Village Financial Management - Abdillah, Raka; Saputra, Dadin Eka; Ridho, M. Rosyid (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Understanding the role of village government in the management and use of village funds, various laws and regulations that regulate it. Where in the management and use of village funds there are many obstacles faced by the village government itself, From the various understandings/definitions, it shows the disharmony of existing laws, so that in practice in the field there will be many obstacles that occur due to these differences. For this reason, the Law on Village Fund Management is a policy related to the role of the village government in managing village funds. This research focuses on two problem formulations, namely what is the role of the Village Government in managing village funds based on Minister of Home Affairs Regulation Number 20 of 2018, and What are the obstacles in managing village funds based on Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Fund Management in Jombang Village. This research is empirical research, which is qualitative. Data collection techniques use observation and interview techniques. The data obtained in this research was analyzed using qualitative descriptive methods. From this study, it was found that the Jombang Village Government has indeed followed the Regulation of the Minister of Home Affairs Number 20 of 2018, but in the management and use of village funds in Jombang Village for the implementation of the use of village funds, it is still not on target. In terms of its role, the Jombang Village Government is still lacking in terms of equipment that is not in accordance with its education, in its management and use, the Jombang Village Government is still less transparent to the community regarding reports on activity realization and reports on accountability realization.